Organotransition metal chemistry - Chatwal, Gurdeep R. (Himalaya Pub. House, 2010)
This book is written according to UGC Curriculum of M.Sc. (Final Year) Chemistry. This text will also be useful to research workers in allied fields who want to become acquainted with the subject. The candidates appearing at NET, GATE and Civil Services Examinations will also be highly benefitted by this book. This text covers the various concepts from bonding to catalysis. This covers the most important developments in organotransition metal chemistry over the last 20 years while retaining the basic concepts and older work. This textbooks is especially suited for the advanced undergraduate or.